ANALISIS TINGKAT KEBERHASILAN PENERAPAN HUMAN RESOURCE INFORMATION SYSTEM (HRIS) MELALUI HUMAN ORGANIZATIONAL TECHNOLOGY (HOT-FIT MODEL) (STUDI KASUS DI PT. KALTIM PARNA INDUSTRI) - Pitta Rose Tina Girsang (JURNAL TEKNOLOGIA, 2021)
This investigation examines the examination of the achievement pace of executing Human Resources Information Systems at PT. Kaltim Parna Industri. HR Information System (HRIS) at PT. Kaltim Parna Industri is generally new creating. Thus, this examination intends to dissect how well the execution of this framework can work appropriately. To gauge the achievement of the utilization of the Human Resources Information System (HRIS) which was as of late carried out at PT. Kaltim Parna Industri, analysts utilized the Human Organization Technology (HOT-fit Model) and recognized the elements that impact the effective execution of the Human Resources Information System (HRIS). The elements of every factor incorporate Human Resources (System Use and User Satisfaction), Organization (Organizational Structure and Organizational Environment), Technology (System Quality, Information Quality, and Service Quality), and Successful Implementation of Human Resources Information Systems (HRIS) (HRIS Performance Acceptance). This investigation utilizes a quantitative methodology. Information assortment methods in research utilizing a survey utilizing a Likert scale (1-5). Assurance of the example in this investigation utilizing the Slovin equation. The example of this examination is 145 representatives of PT. Kaltim Parna Industri. The information assortment method in this examination utilized Probability Sampling which was completed utilizing the Simple Random Sampling strategy. The outcomes showed that there were 30 markers that met the standards in the wake of testing the legitimacy and dependability. From the consequences of the incomplete testing that has been done, it is tracked down that the human asset variable has a positive and critical impact on the achievement of the utilization of the Human Resource Information System, while the authoritative variable has no huge impact on progress. use of Human Resources Information Systems. HR Information System. Be that as it may, innovation factors have a positive and critical impact on the fruitful execution of Human Resources Information System. Keywords: Human Resource Information System, HOT-Fit Model, HRIS